Inhibition of Intestinal Cellular Glucose Uptake by Phenolics Extracted from Whole Wheat Grown at Different Locations. (18th March 2018) - Shamloo, Maryam; Jones, Peter J. H.; Eck, Peter K.
Abstract : Whole grain consumption is associated with reduced risk of type 2 diabetes, and the underlying mechanism might be related to the actions of polyphenols. Dietary polyphenols contribute to low glycemic indices through inhibition of intestinal glucose transport proteins. This study has two objectives: (1) to evaluate how the contents of phenolic acids in wheat vary by genetic background and growth condition and (2) to evaluate how these changes translate into physiologic relevance by investigating cellular glucose transporter inhibitions. Phenolic acids were extracted from wheat varieties grown at different locations over two crop years. The degree of inhibition of glucose uptake into human Caco-2E cells was determined. Free and bound phenolic acid extracts of all wheat genotypes inhibited glucose uptake. Degree of glucose uptake inhibitions positively correlated with the contents of free and bound phenolic acids, and the correlation coefficients wereR 2 = 0.91 andR 2 = 0.89, respectively. Genotype and environment influenced the content of free and bound phenolic acids which linearly translated to the degree of glucose uptake inhibition in a model of intestinal absorption (P < 0.05 ). Results of this work mechanistically support the hypothesis that dietary phenols positively influence the glycemic index and therefore the health properties of whole grain consumption.